Evidence for the Dissemination to Humans of Methicillin-Resistant Staphylococcus aureus ST398 through the Pork Production Chain: A Study in a Portuguese Slaughterhouse - Ons Bouchami; Maria João Fraqueza; Nuno Alexandre Faria; Valquíria Alves; Opeyemi Uwangbaoje Lawal; Herminia de Lencastre; Maria Miragaia (Microorganisms, 2020)
Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) ST398 was recovered from infections in humans exposed to animals, raising public health concerns. However, contact with food producing chain as a means of transmission of LA-MRSA to humans remains poorly understood. We aimed to assess if pork production chain is a source of MRSA ST398 for human colonization and infection. MRSA from live pigs, meat, the environment, and slaughterhouse workers were analyzed by Pulsed-Field Gel Electrophoresis (PFGE), spa, MLST typing, SNPs and for antibiotic resistance and virulence gene profiles. We compared core and accessory genomes of MRSA ST398 isolated from slaughterhouse and hospital. We detected MRSA ST398 (t011, t108, t1451) along the entire pork production chain (live pigs: 60%; equipment: 38%; meat: 23%) and in workers (40%). All MRSA ST398 were multidrug resistant, and the majority carried genes encoding biocide resistance and enterotoxins. We found 23 cross-transmission events between live pigs, meat, and workers (6–55 SNPs). MRSA ST398 from infection and slaughterhouse environment belonged to the same clonal type (ST398, t011, SCCmec V), but differed in 321–378 SNPs. Pork production chain can be a source of MRSA ST398 for colonization of human slaughterhouse workers, which can represent a risk of subsequent meat contamination and human infection.